Applied regression analysis and other multivariable methods - Kleinbaum, David G., author; Kupper, Lawrence L., author; Nizam, Azhar, author; Rosenberg, Eli S., author (Boston, MA : Cengage Learning, 2014)
Includes bibliographical references and index